Languages discourses in Australian middle-class schools: parent and student perspectives. Issue 1 (2nd January 2018) - Wright, Jan; Cruickshank, Ken; Black, Stephen
ABSTRACT: Much of the literature on social class and language study in schools argues that for middle-class parents and their children, languages are chosen for their capacity to offer forms of distinction that provide an edge in the global labour market. In this paper, we draw on data collected from interviews with parents and children in middle-class schools in Australia to demonstrate how a complex amalgam of elite, cultural identity and/or trade language discourses came into play to explain the choice (or not) to study a language and the choice of specific languages. For many of the parents languages provided a limited form of 'civic multiculturalism', as a means of better understanding and respecting the 'other'. We argue that the value attributed to high status languages via this discourse, means their continued presence in schools hoping to attract middle-class parents, but their relative absence in schools with largely working-class populations, where more 'practical' concerns dominate.